Brownian diffusion effect on nanometer aerosol classification in electrical mobility spectrometer - Panich Intra (2018)
A multi-channel differential mobility analyzer (MCDMA) or aerosol spectrometer is widely used for classifying and measuring nanometer aerosol particles in the size range from 1 nm to 1 μm because of its better time response than a typical differential mobility analyzer. In the present study, the effect of Brownian diffusion on electrical mobility classification and trajectory of nanometer aerosol particles in an electrical mobility spectrometer developed at Chiang Mai University has been analytically investigated. Th Brownian diffusion of particles inside the spectrometer increased with decreasing particle size and flow rates of aerosol and clean sheath air, and with increasing inner electrode voltage, and also decreased with decreasing operating pressure. The particle trajectories considering Brownian diffusion motion inside the spectrometer were found to be broader than those under no Brownian diffusion. Smaller particles were found to have higher degree of broadening of trajectory than the larger particles. Brownian diffusion effect was found to be significant for particles smaller than 10 nm. © 2009 Springer.